Towards identifying indigenous personality dimensions of the Malaysian people - Khairul Anwar Mastor,; Zaharah Hassan,; Hasnan Kasan,; Fazilah Idris,; Mohamad Mohsin Mohamad Said,; Fatin Hazwani Siran, (Penerbit Universiti Kebangsaan Malaysia, 2015)
The indigenous personality dimensions of the Malaysian people were investigated by examining: (a) the trait adjective nouns provided by the cultural informants; (b) factor analyses of the items and factors capturing the personality trait adjectives. University undergraduate students of different racial background (N= 250) completed an open ended questionnaire about common personality trait adjectives and their associated behavioral exemplars. More than 20 desirable and non-desirable personality trait adjectives were identified through the open-ended questionnaire After selecting and refining the most frequently cited personality trait adjectives, items were developed based on the given behavioral and situational examples. In the following study, 1087 other university students completed the personality questionnaire. We combined the items of desirable and undesirable traits and factor analyze the 419 items in a series of incremental factor rotations. Congruence indices suggest the existence 4 factors of personality dimension. Good reliability and interpretable factors provide sufficient support for the indigenous dimensions of personality traits among Malaysians. Further comprehensive study involving relating the dimensions to the universal model of personality is recommended.